AIE luminogens: emission brightened by aggregation. Issue 7 (September 2015) - Wang, Hong; Zhao, Engui; Lam, Jacky W.Y.; Tang, Ben Zhong
<x xml:space="preserve">Abstract</x> Luminogens with the feature of aggregation-induced emission (AIE) are a class of 'heterodox' molecules, whose emissions are brightened by aggregate formation. The restriction of their intramolecular motions in an aggregate state is the main cause of the AIE process. In this account, we summarize recent progress in exploring high-tech applications of AIE luminogens (AIEgens) as biological sensors, chemical probes, optoelectronic devices, and intelligent materials. Our discussion is focused on mechanistic analysis, classifying the electronic interactions involved into three categories: (a) through-bond, (b) through-space, and (c) through-bond and -space conjugations. Such a mechanistic understanding will help guide further development of new AIEgens and their applications.